2001
DOI: 10.1080/09593332208618266
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Leachate Pretreated in an Upflow Anaerobic Sludge Blanket Reactor

Abstract: This study was conducted to develop a two-stage process for the treatment of Hong Kong leachate. The leachate, containing 4750 mg l-1 of chemical oxygen demand (COD) and 1310 mg l-1 of ammoniacal nitrogen (NH3-N), was first treated in a UASB (upflow anaerobic sludge blanket) reactor at 37 degrees C. The process removed on average 66.1% of COD with 6.1 days of hydraulic retention time (HRT), corresponding to an organic loading rate of 0.78 g-COD (l.day)-1. The UASB effluent, which had an average pH of 8.9, COD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…In our experiments, N-NO 2 À , N-NO 3 À , and N-NH 4 þ concentrations practically did not change after the Fenton process, for the different pH values tested (Table 2). This is in agreement with the results of Wang et al (2001). Other studies reported that only with high H 2 O 2 concentrations in the Fenton process eliminate ammonium and the main by-products are gaseous N 2 and nitrate (Goi and Trapido, 2002).…”
Section: Fenton Treatmentsupporting
confidence: 92%
“…In our experiments, N-NO 2 À , N-NO 3 À , and N-NH 4 þ concentrations practically did not change after the Fenton process, for the different pH values tested (Table 2). This is in agreement with the results of Wang et al (2001). Other studies reported that only with high H 2 O 2 concentrations in the Fenton process eliminate ammonium and the main by-products are gaseous N 2 and nitrate (Goi and Trapido, 2002).…”
Section: Fenton Treatmentsupporting
confidence: 92%
“…Les études existantes portent sur des lixiviats « jeunes » avec de fortes concentrations en DCO (QUAN et al, 2013) et des lixiviats « matures » qui présentent un rapport de biodégradabilité (DBO/DCO) faible (FEKI et al, 2009). Il est à noter que, dans ce couplage, le procédé d'électro-oxydation est généralement placé en aval du traitement biologique (ANGLADA et al, 2010;FEKI et al, 2009;FERNANDES et al, 2012;QUAN et al, 2013;WANG et al, 2001;XIAO et al, 2013). Ce choix peut être justifié du fait qu'il peut y avoir un phénomène de compétition entre la dégradation électrochimique des composés réfractaires et celle des composés biodégradables.…”
Section: Couplage éLectro-oxydation Et Traitement Biologiqueunclassified
“…Second, the high chloride content could facilitate indirect bulk oxidation through the electrogeneration of strong oxidants such as hypochlorite [13]. Third, oxidation of recalcitrant organics can be accomplished concomitantly [14].…”
Section: Introductionmentioning
confidence: 99%
“…Electro-oxidation has been successfully implemented for the abatement of hard-to-treat wastes such as landfill leachate [13,14], textile effluent [15] [16]. Particularly with regard to RO brine, it has several advantageous features: first, the elevated salinity of RO concentrate ensures an excellent electric conductivity (EC) that could lower the energy consumption [17].…”
Section: Introductionmentioning
confidence: 99%